Cholestatic jaundice revealing pylephlebitis associated with mesenteric venous thrombosis - Chávez-Sánchez, Siomara Aransuzú (2026)
Mesenteric venous thrombosis is an uncommon but highly morbid condition with nonspecific clinical manifestations that may delay early diagnosis. We report the case of a 65-year-old man with a history of venous insufficiency and chronic smoking, who presented with abdominal pain, jaundice, and fever. Imaging revealed extensive thrombosis of the superior mesenteric vein, pylephlebitis, and heterozygous C677T MTHFR mutation. The patient was treated with antibiotics, anticoagulation, and transhepatic portal thrombectomy minimally invasive with thrombolysis, showing favorable clinical and biochemical recovery. This case highlights the importance of considering both infectious and prothrombotic conditions in patients with abdominal pain and jaundice, emphasizing the role of a multidisciplinary approach.